Chemometric Investigation and Antimicrobial Activity of Salvia rosmarinus Spenn Essential Oils - Saoussan Annemer; Abdellah Farah; Hamide Stambouli; Amine Assouguem; Mikhlid H. Almutairi; Amany A. Sayed; Ilaria Peluso; Taoufik Bouayoun; Nehal Ahmed Talaat Nouh; Abdelhakim El Ouali Lalami; Yassine Ez zoubi (Molecules, 2022)
To ensure the better production and sustainable management of natural resources, a chemometric investigation was conducted to examine the effect of cooperative and harvesting periods on the crop yields and chemical compositions of Salvia rosmarinus Spenn essential oils in the Oriental region of Morocco. The samples were collected from three cooperatives over nine time periods from January 2018 to April 2019. The chemical composition of Salvia rosmarinus Spenn essential oils was analyzed by gas chromatography coupled with mass spectrometry. The data from this study were processed by multivariate analyses, including principal component analysis (PCA) and hierarchical cluster analysis (HCA). The disc diffusion technique and a determination of the minimal inhibitory concentration were performed to study the antibacterial properties of the oils. Statistical analysis showed that the cooperative and harvest period have a significant effect on yields. The highest yield of essential oil was recorded in April 2019 at cooperative C1. The PCA and the HCA results were divided into two groups: Group A for the summer season and group B for the winter season. The samples collected during summer were characterized by a high amount of 1,8-cineole component and a high yield of essential oil, whereas the samples collected during winter were qualified by a high amount of α-pinene component and a low yield of essential oil. The antibacterial activity of Salvia rosmarinus Spenn essential oils showed that Mycobacterium smegmatis ATCC23857 and Bacillus subtilis ATCC 23857 are the most susceptible strains, stopping growth at 1/500 (v/v). The least susceptible strain is Escherichia coli ATCC25922, with an MIC value corresponding to 1/250 (v/v). The findings of this study could have a positive economic impact on the exploitation of rosemary in the Oriental region, especially during the best harvest periods, as they indicate how to obtain the best yields of oils richest in 1,8-cineole and α-pinene chemotypes.